1996
DOI: 10.1677/joe.0.1480139
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 effect on glycemia in the non-obese diabetic mouse at the pre-diabetic stage

Abstract: Cytokines, particularly interleukin 1 (IL-1) and tumor necrosis factor, are known to induce hypoglycemia in normal rodents or different experimental models of type II diabetes. We investigated, at the pre-diabetic stage, the effect of short-term administration of murine recombinant interleukin-1 alpha (mrIL-1 alpha) on the levels of glucose, insulin and corticosterone in the non-obese diabetic (NOD) mouse, a spontaneous model of type I diabetes. Two-month-old, pre-diabetic NOD mice of both sexes were insensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 39 publications
3
21
0
Order By: Relevance
“…Blood glucose levels 20 -60 min after intravenous glucose infusions were significantly lower in 6-week-old NOD mice compared with the control (Fig. 1A), which suggested an excessive insulin release, as has been previously proposed (3,26). The Ca 2ϩ clearance and glucosestimulated calcium oscillations of individual NOD beta-cells were not significantly different from those of Balb/c cells (Figs.…”
Section: Discussionsupporting
confidence: 76%
“…Blood glucose levels 20 -60 min after intravenous glucose infusions were significantly lower in 6-week-old NOD mice compared with the control (Fig. 1A), which suggested an excessive insulin release, as has been previously proposed (3,26). The Ca 2ϩ clearance and glucosestimulated calcium oscillations of individual NOD beta-cells were not significantly different from those of Balb/c cells (Figs.…”
Section: Discussionsupporting
confidence: 76%
“…However, in those experiments 2-month-old mice were analyzed, and at this age the islets of NOD mice are already fully infiltrated by lymplocytes. It was suggested that the production of inflammatory cytokines such as IL-1 in the insulitic islets is a crucial contributing factor to the insulin resistance (15).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, in two other models of autoimmunity, the diabetic BB rat and the Obese chicken, a model of Hashimoto's thyroiditis, an altered affinity of corticosteroid-binding globulin (CBG) caused by a point mutation and an elevated level of CBG, respectively, were reported [27,28]. Likewise, NOD mice develop an abnormal corticosterone response to a stimulation by IL-1a [29]. Such alterations of the immune endocrine system could influence autoimmune susceptibility by modulating sensitivity of autoreactive clones to apoptosis independently of their intrinsic resistance to PCD.…”
Section: Discussionmentioning
confidence: 99%